Secondary doped polymer coated silicon-carbon composite material and preparation method thereof
By using a secondary doped polymer-coated silicon-carbon composite material in lithium-ion batteries, the problems of carbon layer failure and polymer coating in the prior art are solved, and high cycling stability of the material is achieved and rate performance, suitable for industrial production.
Patent Information
- Application Number
- CN202510022601.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Prior Art When using high-temperature pyrolytic phenolic resin polymer to form a carbon layer in lithium-ion batteries, the carbon layer is destroyed due to the stress generated by the volume expansion of silicon, and the method of direct polymer coating is difficult to ensure the uniformity of the coating layer. , cannot effectively support the volume expansion of silicon during long-term circulation.
The preparation method of the silicon-carbon composite material coated with secondary doped polymers is adopted. By providing carbon material composite with nano-silicon combined with porous structures as a substrate, the porous carbon framework limits the volume expansion of silicon and polymerizes in situ on the surface of the substrate. Coated with highly elastic polymers, dedoping and lithium salt secondary doping are performed to form a continuous conductive pathway and a stable solid electrolyte interface layer.
It significantly improves the circulation and rate performance of the material, reduces the specific surface area, reduces the preparation cost, and is suitable for industrial production.
Smart Images

Figure CN119430189A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a secondary doped polymer-coated silicon-carbon composite material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries, also known as secondary batteries, are one of the current mainstream energy storage devices and are widely used in electric vehicles, energy storage devices, portable electronic products and other fields. The surge in energy demand has stimulated the rapid development of lithium-ion batteries. Silicon has become the most promising negative electrode material due to its high energy density, low discharge platform, and abundant natural reserves. However, the electronic conductivity of silicon negative electrodes is poor, and the process of lithium ion insertion and deinsertion is accompanied by a huge volume expansion (~300%), causing the material particles to shatter and crack, and even lose electrical contact with the current collector. The continuously updated solid electrolyte interface layer also greatly increases the irreversible capacity and reduces the battery cycle life. Therefore, the research on the use of silicon in lithium-ion batteries needs to overcome the shortcomings of silicon's poor conductivity and significant volume expansion effect.
[0003] Prior art 1 (patent application number CN202310848485.9) discloses: a method for preparing a carbon-coated porous silicon negative electrode material for lithium-ion batteries, wherein magnesium silicide is first subjected to a hydrothermal reaction at high temperature, and then the product is pickled to remove magnesium salts and impurities to obtain a light yellow powder. Then, a phenolic resin polymer is grown in situ in an alkaline aqueous solution, and then a dense carbon shell is formed by high-temperature pyrolysis, which is then uniformly coated on porous silicon particles, thereby effectively alleviating the volume change of silicon during the cycle, improving the cycle stability and the conductivity of the composite material. At the same time, the porous structure provides a large number of active sites for lithium ions, which helps to improve its electrochemical stability. The prepared carbon-coated porous silicon is used as a negative electrode material in lithium-ion batteries, which has a significant effect on improving the specific capacity, cycle performance and rate performance of lithium-ion batteries, and the process is simple, environmentally friendly and low-cost.
[0004] However, this method forms a carbon layer on the surface of porous silicon by pyrolyzing phenolic resin polymer at high temperature. During the cycle, the rigid carbon layer will be destroyed and cannot be repaired due to the stress generated by the volume expansion of silicon, making it difficult to maintain the integrity of the electrode structure, resulting in performance degradation. The capacity retention rate is less than 40% after 120 cycles at a current density of 0.5C. In addition, the use of high-temperature hydrothermal method and acid washing to prepare porous silicon is difficult to apply on a large scale.
[0005] Prior art 2 (patent application number CN201810379550.7) discloses: a method for preparing a conductive polymer-coated silicon-carbon composite negative electrode material. The present invention discloses a method for preparing a conductive polymer-coated silicon-carbon composite negative electrode material, comprising the following steps: (1) dissolving a conductive polymer in a solvent in the presence of a surface dispersant to obtain a solution; (2) weighing nano-silicon and flake graphite in a certain proportion and adding them to the above solution for uniform dispersion; (3) evaporating the dispersion obtained in step (2) at a certain temperature to obtain a solid phase precursor; (4) drying the obtained precursor in a blast drying oven at 60-80°C; (5) grinding the precursor into powder, sieving it, and then performing high-temperature pyrolysis in a nitrogen-protected tubular furnace, heating it to 600-800°C at a rate of 3-7°C / min, and keeping the temperature constant for 3-5h, and then cooling it to below 100°C with the furnace to obtain a silicon-carbon composite material. By adopting the method of the present invention, the conductive polymer coating is utilized to not only improve the conductivity of the material, but also form a three-dimensional network structure with a certain strength to overcome the volume expansion problem of silicon and meet the use requirements.
[0006] In this method, nano-silicon is expensive and easy to agglomerate, and it is difficult to disperse evenly with flake graphite. Direct polymer coating is difficult to ensure the uniformity of the coating layer, which is insufficient to support the volume expansion of silicon during long-term circulation.
[0007] Therefore, the existing technology needs to be improved. Summary of the invention
[0008] In the prior art method for solving the expansion effect of silicon in lithium-ion batteries, a method of forming a carbon layer on the surface of porous silicon by high-temperature pyrolysis of phenolic resin polymer will result in the rigid carbon layer being destroyed and unable to be repaired due to the stress generated by the volume expansion of silicon; and direct polymer coating is difficult to ensure the uniformity of the coating layer, which is insufficient to support the volume expansion of silicon during long-term cycles. Therefore, the present invention provides a secondary doped polymer-coated silicon-carbon composite material and a preparation method thereof, and a lithium-ion battery for solving the problem of the expansion effect of silicon in lithium-ion batteries.
[0009] To achieve the above object, in a first aspect, the present invention provides a method for preparing a secondary doped polymer-coated silicon-carbon composite material, which comprises the following specific steps: S1. providing a silicon-carbon substrate, wherein the silicon-carbon substrate is obtained by mixing a porous carbon precursor and a silicon source and sintering the mixture at 400-700° C.; S2, providing an acid-doped polymer to form an acid-doped polymer coating layer on the surface of the silicon-carbon substrate to obtain a polymer-coated silicon-carbon composite material; S3, adding an alkaline solution to dedope the polymer-coated silicon-carbon composite material; S4. Add lithium salt for secondary doping to obtain the desired silicon-carbon composite material.
[0010] In one implementation, in S1, the silicon carbon substrate has a porous structure and the pores contain silicon nanoparticles, the size of the pores is 0.1-100 nm, and the size of the silicon nanoparticles is 0.1-50 nm.
[0011] In one implementation, in S2, specifically including: adding the silicon-carbon substrate to ethanol, adding a silane coupling agent after stirring and refluxing, the reflux temperature is 0°C~100°C, the reflux time is 0.5~3h, adding acid and polymer monomer and stirring evenly to obtain solution A; slowly adding ammonium persulfate solution to solution A, reacting for 2~8h, after the reaction is completed, washing the obtained mixed solution with ethanol / distilled water alternately, filtering it three times, and then drying it completely in a vacuum environment at 80°C to obtain a polymer-coated silicon-carbon composite material.
[0012] In one implementation, in S2, the acid includes any one of hydrochloric acid, sulfuric acid, phosphoric acid, perchloric acid, nitric acid, hydrobromic acid, dodecylbenzenesulfonic acid, salicylic acid, benzoic acid, citric acid and oxalic acid.
[0013] In one implementation, in S2, the polymer monomer may be any one of aniline, pyrrole and thiophene.
[0014] In one implementation, in S2, the silane coupling agent includes any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, aminoethylaminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and vinyltri(2-methoxyethoxy)silane.
[0015] In one implementation, in S3, the alkaline solution includes any one of aqueous ammonia, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution and hydrazine hydrate.
[0016] In one implementation, in S4, the lithium salt includes any one of lithium metaborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate) and lithium chloride.
[0017] In a second aspect, the present invention further provides a secondary doped polymer-coated silicon-carbon composite material, which is prepared by the preparation method of the secondary doped polymer-coated silicon-carbon composite material described in the present invention.
[0018] In a third aspect, the present invention further provides a lithium-ion battery, which comprises the secondary doped polymer-coated silicon-carbon composite material provided by the present invention.
[0019] Beneficial effects: In the preparation method of the secondary doped polymer-coated silicon-carbon composite material provided by the present invention, a composite of nano-silicon combined with a porous structure carbon material is provided as a substrate, wherein the porous carbon skeleton can limit the volume effect of silicon while enhancing the conductivity of the material, and the nano-scale silicon particles can achieve long cycle stability; further, the polymer is in situ polymerized and coated on the surface of the substrate, and the defect of large rigidity of the carbon coating layer is compensated by the highly elastic polymer coating layer, while reducing the direct contact between the electrolyte and the silicon nanoparticles, reducing side reactions, and helping to form a stable solid electrolyte interface layer to prevent further decomposition of the electrolyte; then dedoping and secondary lithium salt doping are carried out, and the re-growth of the polymer molecular chain is promoted by secondary doping, and the steric hindrance makes the surface polymer layer easier to be doped, thereby forming a continuous conductive path, improving the conductivity, providing more ion transmission channels, improving the diffusion rate of lithium ions in the electrode material, and improving the rate performance. The material prepared by the preparation method of the secondary doped polymer-coated silicon-carbon composite material provided by the present invention has greatly improved cycle and rate performance, greatly reduced specific surface area, low preparation cost and simple operation, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flow chart of the steps of the preparation method of the secondary doped polymer-coated silicon-carbon composite material provided by the present invention; Figure 2 This is a 1C cycle performance diagram of the secondary doped polymer-coated silicon-carbon composite material provided by the present invention; Figure 3 It is a rate performance diagram of the secondary doped polymer-coated silicon-carbon composite material provided in Example 1 and Example 3 of the present invention; Figure 4 1 is an electrochemical impedance diagram of the secondary doped polymer-coated silicon-carbon composite material provided in Example 3 of the present invention and Comparative Example 1; Figure 5 GITT diagram of the secondary doped polymer-coated silicon-carbon composite material provided in Example 3 of the present invention and Comparative Example 1; Figure 6 It is a curve diagram showing the change of conductivity of the secondary doped polymer-coated silicon-carbon composite material with pressure provided by the present invention; Figure 7 This is the FT-IR graph of the secondary doped polymer-coated silicon-carbon composite material provided by the present invention; Figure 8 This is an XPS graph of the secondary doped polymer-coated silicon-carbon composite material provided in an embodiment of the present invention.
[0021] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0023] Read more Figure 1 , Figure 1 The present invention provides a method for preparing a secondary doped polymer-coated silicon-carbon composite material, which comprises the following specific steps: S1. providing a silicon-carbon substrate, wherein the silicon-carbon substrate is obtained by mixing a porous carbon precursor and a silicon source and sintering the mixture at 400-700° C.; S2, providing an acid-doped polymer to form an acid-doped polymer coating layer on the surface of the silicon-carbon substrate to obtain a polymer-coated silicon-carbon composite material; S3, adding an alkaline solution to dedope the polymer-coated silicon-carbon composite material; S4. Add lithium salt for secondary doping to obtain the desired silicon-carbon composite material.
[0024] Specifically, in S1, the silicon carbon substrate has a porous structure and contains silicon nanoparticles in the pores, the size of the pores is 0.1-100 nm, and the size of the silicon nanoparticles is 0.1-50 nm. In this step, the sintering temperature is 400-700°C, preferably, the sintering temperature is 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C.
[0025] In S1, the preparation process of the silicon-carbon substrate specifically includes: adding a carbon source into a chemical vapor deposition furnace (CVD furnace), introducing an inert gas, and maintaining for 60 minutes. Then, adjusting the temperature in the furnace for sintering, introducing a silicon source, maintaining for a period of time, and then introducing a carbon source gas, maintaining for a period of time, to obtain the silicon-carbon substrate.
[0026] Wherein, the inert gas includes any one of nitrogen, argon and hydrogen, and the flow rate of the inert gas is 1 to 20 L / min. Preferably, the flow rate of the inert gas is 1 L / min, 2 L / min, 4 L / min, 8 L / min, 10 L / min, 14 L / min, 18 L / min or 20 L / min.
[0027] Specifically, the silicon source gas includes any one of monosilane, disilane and silane derivatives. The flow rate of the silicon source gas is 0.5-10 L / min, preferably, the flow rate of the silicon source gas is 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min or 10 L / min. The time for introducing the silicon source gas is 100-1000 min, preferably, the time for introducing the silicon source gas is 100 min, 200 min, 300 min, 400 min, 500 min, 600 min, 700 min or 1000 min.
[0028] Specifically, the carbon source gas includes any one of acetylene, ethylene and methane. The speed of introducing the carbon source gas is 1~10L / min, preferably, the speed of introducing the carbon source gas is 1L / min, 2L / min, 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min or 10L / min, etc. Further, the carbon coating temperature is 500~800℃ when the carbon source is introduced, preferably, the temperature in the furnace can be increased to 500℃, 550℃, 600℃, 650℃, 700℃, 750℃ or 800℃, etc. Further, the time of introducing the carbon source gas is 50~500min, preferably, the time of introducing the carbon source gas is 50min, 100min, 150min, 200min, 250min, 300min, 350min, 400min, 450min or 500min, etc.
[0029] In S2, it specifically includes: adding the silicon-carbon substrate to ethanol, adding a silane coupling agent after stirring and refluxing, the reflux temperature is 0°C~100°C, the reflux time is 0.5~3h, adding acid and polymer monomer and stirring evenly to obtain solution A; slowly adding ammonium persulfate solution to solution A, reacting for 2~8h, after the reaction is completed, washing the obtained mixed solution with ethanol / distilled water alternately, filtering it three times, and drying it completely in a vacuum environment at 80°C to obtain a polymer-coated silicon-carbon composite material.
[0030] Specifically, the acid includes any one of hydrochloric acid, sulfuric acid, phosphoric acid, perchloric acid, nitric acid, hydrobromic acid, dodecylbenzenesulfonic acid, salicylic acid, benzoic acid, citric acid and oxalic acid. The polymer monomer can be any one of aniline, pyrrole and thiophene. Further, the polymer coating layer thickness is 1~20nm. The silane coupling agent includes any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, aminoethylaminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and vinyltri(2-methoxyethoxy)silane.
[0031] In S3, it specifically includes: putting the composite material obtained in S2 into an alkaline solution, stirring for 2 to 6 hours, washing and filtering three times with ethanol / distilled water alternately, and drying completely in a vacuum environment at 80°C to obtain a dedoped polymer-coated silicon-carbon composite material.
[0032] Specifically, the alkaline solution includes any one of ammonia water, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution and hydrazine hydrate. The amount of the dedoped alkaline solution is 0.1% to 1% of the polymer-coated silicon-carbon composite material. For example, the amount of ammonia water is 0.1%, 0.25%, 0.5%, and 1%.
[0033] In S4, specifically including: putting the composite material obtained in S3 into water, stirring and dispersing, then adding lithium salt, stirring for 2-8 hours, washing and filtering three times with ethanol / distilled water alternately, and drying completely in a vacuum environment at 80°C to obtain the desired silicon-carbon composite material.
[0034] Specifically, the lithium salt includes any one of lithium metaborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate) and lithium chloride.
[0035] The present invention also specifically illustrates the technical solution of the present invention through multiple embodiments and comparative examples.
[0036] Embodiment 1: 3000 g of porous carbon was added to the CVD furnace, and nitrogen was introduced at a flow rate of 14 L / min for 60 min. The temperature in the CVD furnace was raised to 520°C, and monosilane was introduced at a flow rate of 3 L / min for 500 min, and acetylene gas was introduced at a flow rate of 3 L / min for 200 min to obtain a silicon-carbon substrate.
[0037] Embodiment 2: S1. Add 3000 g of porous carbon into a CVD furnace, introduce nitrogen at a flow rate of 14 L / min, and maintain for 60 min. Raise the temperature in the CVD furnace to 520°C, introduce monosilane at a flow rate of 3 L / min, and continue to introduce it for 500 min, and introduce acetylene gas at a flow rate of 3 L / min, and continue to introduce it for 200 min to obtain a silicon-carbon substrate.
[0038] S2. Weigh 20 g of the obtained silicon-carbon substrate and add it into ethanol for magnetic stirring. Add silane coupling agent and reflux for 3 hours at a reflux temperature of 80°C. Add a certain amount of 2M phosphoric acid solution and 2 ml aniline solution in sequence and stir evenly to obtain solution A. Slowly add 1M ammonium persulfate solution into solution A and polymerize in situ for 5 hours. After the reaction is completed, wash the obtained mixed solution with ethanol and deionized water alternately and filter it three times, then dry it completely in a vacuum environment at 80°C to obtain an acid-doped polyaniline-coated silicon-carbon composite material.
[0039] S3. Weigh 10 g of the above-mentioned acid-doped composite material, put it into 100 ml of 0.1 M ammonia water, stir for 4 h, wash and filter it three times with ethanol / distilled water alternately, and dry it completely in a vacuum environment at 80°C to obtain a dedoped polyaniline-coated silicon-carbon composite material.
[0040] S4. Weigh 7 g of the above dedoped composite material and put it into 70 ml of deionized water, stir and disperse it, add 1% lithium metaborate, stir for 5 hours, wash and filter it three times with ethanol / distilled water alternately, and dry it completely in a vacuum environment at 80°C to obtain a secondary doped polyaniline-coated silicon-carbon composite material.
[0041] Embodiment 3: Different from Example 2, in this embodiment, in the step of dedoping the polymer-coated silicon-carbon composite material, 10 g of the above-mentioned acid-doped composite material is weighed and placed in 100 ml of 0.25 M ammonia water for dedoping. The other implementation steps are the same as those in Example 2 and will not be repeated here.
[0042] Embodiment 4: Different from Example 2, in this embodiment, in the step of dedoping the polymer-coated silicon-carbon composite material, 10 g of the above-mentioned acid-doped composite material is weighed and placed in 100 ml of 0.5 M ammonia water for dedoping. The other implementation steps are the same as those in Example 2 and will not be repeated here.
[0043] Embodiment 5: Different from Example 2, in this embodiment, in the step of dedoping the polymer-coated silicon-carbon composite material, 10 g of the above-mentioned acid-doped composite material is weighed and placed in 100 ml of 1M ammonia water for dedoping. The other implementation steps are the same as those in Example 2 and will not be repeated here.
[0044] Comparative Example 1: 3000 g of porous carbon was added to the CVD furnace, and nitrogen was introduced at a flow rate of 14 L / min for 60 min. The temperature in the CVD furnace was raised to 520°C, and monosilane was introduced at a flow rate of 3 L / min for 500 min. In this comparative example, no carbon source gas was introduced to obtain an uncoated silicon-carbon substrate.
[0045] Comparative Example 2: Provide the silicon-carbon substrate in Example 1, weigh 20 g of the silicon-carbon substrate, add it into ethanol and perform ultrasound, drop 4 ml of ammonia water for magnetic stirring, then drop 5 ml of ethanol solution containing isopropyl titanium, react for 8 hours, centrifuge and dry completely in a vacuum environment at 80°C, calcine at 550°C under Ar atmosphere for 3 hours to obtain a titanium dioxide-coated silicon-carbon material.
[0046] Comparative Example 3: Nitrogen was introduced into the CVD furnace at a flow rate of 14 L / min and maintained for 30 min. The temperature in the CVD furnace was raised to 520° C., monosilane was introduced at a flow rate of 3 L / min, and acetylene gas was introduced at a flow rate of 3 L / min for 300 min to obtain a nano-silicon-carbon composite material.
[0047] Comparative Example 4: Different from Example 2, in this example, only the acid-doped polyaniline-coated silicon-carbon composite material in S2 is obtained, and the specific steps are the same as those in Example 2, which will not be repeated here.
[0048] Comparative Example 5: Different from Example 2, in this example, only the dedoped polyaniline-coated silicon-carbon composite material in S3 is obtained, and the specific steps are the same as those in Example 2, which will not be repeated here.
[0049] Comparative Example 6: Different from Example 2, in this embodiment, after obtaining the silicon-carbon substrate in S1, 20 g of the obtained silicon-carbon substrate was weighed and added to ethanol for magnetic stirring, a silane coupling agent was added and refluxed for 3 hours, the reflux temperature was 80°C, 1 g of doped polyaniline was added, and the reaction was performed for 5 hours. After the reaction was completed, the obtained mixed solution was washed with ethanol and deionized water alternately and filtered three times, and then placed in a vacuum environment at 80°C to completely dry, and a silicon-carbon composite material coated with doped polyaniline was obtained. The coated polymer in this comparative example was not acid-doped.
[0050] Comparative Example 7: Different from Example 2, in this example, after obtaining the silicon-carbon substrate in S1, 20 g of the obtained silicon-carbon substrate was weighed and added to ethanol for magnetic stirring, and a certain amount of 2M phosphoric acid solution and 2 ml aniline solution were added in sequence and stirred evenly to obtain solution A; 1M ammonium persulfate solution was slowly added to solution A, and in-situ polymerization was performed for 5 hours. After the reaction was completed, the obtained mixed solution was washed with ethanol and deionized water alternately and filtered three times, and then placed in a vacuum environment at 80°C and dried completely to obtain a silicon-carbon composite material coated with acid-doped polyaniline without a coupling agent. No silane coupling agent was added to the coated polymer in this comparative example.
[0051] Part of the data of the above examples and comparative examples can be seen Figure 2~Figure 8 ,in, Figure 2 This is the 1C cycle performance diagram of the secondary doped polymer-coated silicon-carbon composite material provided by the present invention, Figure 3 is a rate performance diagram of the secondary doped polymer-coated silicon-carbon composite material provided in Examples 1 and 3 of the present invention, Figure 4 : is the electrochemical impedance diagram of the secondary doped polymer-coated silicon-carbon composite material provided in Example 3 of the present invention and Comparative Example 1, Figure 5 is the GITT diagram of the secondary doped polymer-coated silicon-carbon composite material provided in Example 3 of the present invention and Comparative Example 1, Figure 6 is a curve diagram showing the change of conductivity of the secondary doped polymer-coated silicon-carbon composite material with pressure, provided by the present invention. Figure 7 This is the FT-IR graph of the secondary doped polymer-coated silicon-carbon composite material provided by the present invention, Figure 8 This is an XPS graph of the secondary doped polymer-coated silicon-carbon composite material provided in an embodiment of the present invention.
[0052] Electrochemical performance test: Electrode preparation: weigh the above composite material, conductive carbon black, and binder CMC in proportion, add deionized water to prepare a uniform slurry, wherein the solid content ratio of composite material: conductive carbon black: binder CMC is 95:1.5:3.5, and use a homogenizer to make the sample at a speed of 2000 rpm for 20 min.
[0053] The slurry was sieved and evenly coated on the copper foil, and placed in a 90°C vacuum drying oven for drying. The dried electrode was rolled and cut into circular electrodes of a certain size, and the electrode mass was recorded.
[0054] Button battery assembly: In an argon atmosphere glove box, a metal lithium sheet is used as a counter electrode and assembled into a button battery with the above-obtained electrode, diaphragm, gasket, etc., and a silicon-carbon special electrolyte is used as the electrolyte.
[0055] pass Figure 2 The data results are summarized in Table 1.
[0056] Table 1: Figure 2 The performance test results of the embodiments and comparative examples shown are: .
[0057] From Table 1 and Figure 2 It can be seen that the secondary doped polyaniline-coated silicon-carbon composite material provided in Example 3 has a first-cycle reversible capacity of 1752.1 mAh / g and a first coulombic efficiency of 91.88%. After 200 cycles, the reversible capacity is 1008.1 mAh / g and the capacity retention rate is 71.12%, which has excellent cycle performance and first-cycle coulombic efficiency.
[0058] In summary, in the technical solution provided by the present invention, a silicon-carbon material containing nano-silicon nanoparticles in the porous carbon pores is used as the substrate, and the porous structure can limit the expansion of silicon and reduce the damage to the electrode structure caused by volume change; the acid-doped polymer is in situ polymerized and coated on the surface of the substrate, and the modification of the substrate surface by the silane coupling agent can not only improve the dispersibility of the substrate, but also use the surface group as the initiation site for polymerization to initiate polymerization, synthesize a highly conductive polymer shell layer, and connect the coating layer to the silicon-carbon substrate in the form of covalent bonds; the heteroatoms in the polymer can cause defects around it while improving the conductivity of the composite material, and these defects can provide additional lithium storage capacity; the coating layer can greatly improve the conductivity of the composite material, and the coating layer can also ... Reduce the specific surface area of the material. Low specific surface area can effectively reduce agglomeration and promote lithium ion diffusion. On the other hand, the highly elastic conductive polymer can accommodate the volume expansion of silicon, reduce the direct contact between the electrolyte and silicon nanoparticles, thereby reducing side reactions, and help form a stable solid electrolyte interface layer to prevent further decomposition of the electrolyte; then dedoping and secondary doping with lithium salts are carried out. Secondary doping can promote the regrowth of polymer molecular chains, and the steric hindrance makes the surface polymer layer easier to be doped, thereby forming a continuous conductive path, improving the conductivity (1.25 times), providing more ion transmission channels, improving the diffusion rate of lithium ions in the electrode material, and improving the rate performance.
[0059] The method for preparing the composite material provided by the present invention has greatly improved cycle and rate performance of the prepared material, greatly reduced specific surface area, low preparation cost and simple operation, and is suitable for industrial production.
[0060] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a secondary doped polymer-coated silicon-carbon composite material, characterized in that: The specific steps include: S1. providing a silicon-carbon substrate, wherein the silicon-carbon substrate is obtained by mixing a porous carbon precursor and a silicon source and sintering the mixture at 400-700° C.; S2, providing an acid-doped polymer to form an acid-doped polymer coating layer on the surface of the silicon-carbon substrate to obtain a polymer-coated silicon-carbon composite material; S3, adding an alkaline solution to dedope the polymer-coated silicon-carbon composite material; S4. Add lithium salt for secondary doping to obtain the desired silicon-carbon composite material.
2. The method for preparing the secondary doped polymer-coated silicon-carbon composite material according to claim 1, characterized in that: In S1, the silicon carbon substrate has a porous structure and the pores contain silicon nanoparticles, the size of the pores is 0.1-100 nm, and the size of the silicon nanoparticles is 0.1-50 nm.
3. The method for preparing the secondary doped polymer-coated silicon-carbon composite material according to claim 1, characterized in that: In S2, it specifically includes: adding the silicon-carbon substrate to ethanol, adding a silane coupling agent after stirring and refluxing, the reflux temperature is 0°C~100°C, the reflux time is 0.5~3h, adding acid and polymer monomer and stirring evenly to obtain solution A; slowly adding ammonium persulfate solution to solution A, reacting for 2~8h, after the reaction is completed, washing the obtained mixed solution with ethanol / distilled water alternately, filtering it three times, and drying it completely in a vacuum environment at 80°C to obtain a polymer-coated silicon-carbon composite material.
4. The method for preparing the secondary doped polymer-coated silicon-carbon composite material according to claim 1, characterized in that: In S2, the acid includes any one of hydrochloric acid, sulfuric acid, phosphoric acid, perchloric acid, nitric acid, hydrobromic acid, dodecylbenzenesulfonic acid, salicylic acid, benzoic acid, citric acid and oxalic acid.
5. The method for preparing the secondary doped polymer-coated silicon-carbon composite material according to claim 1, characterized in that: In S2, the polymer monomer may be any one of aniline, pyrrole and thiophene.
6. The method for preparing the secondary doped polymer-coated silicon-carbon composite material according to claim 3, characterized in that: In S2, the silane coupling agent includes any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, aminoethylaminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and vinyltri(2-methoxyethoxy)silane.
7. The method for preparing the secondary doped polymer-coated silicon-carbon composite material according to claim 1, characterized in that: In S3, the alkaline solution includes any one of ammonia water, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution and hydrazine hydrate.
8. The method for preparing the secondary doped polymer-coated silicon-carbon composite material according to claim 1, characterized in that: In S4, the lithium salt includes any one of lithium metaborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate) and lithium chloride.
9. A secondary doped polymer-coated silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the method for preparing the secondary doped polymer-coated silicon-carbon composite material according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It includes the secondary doped polymer-coated silicon-carbon composite material as described in claim 9.
Citation Information
Patent Citations
Method for preparing conductive polymer coated silicon-carbon composite cathode material
CN108807871A
Preparation method of carbon-coated porous silicon negative electrode material for lithium ion battery
CN116826000A
Silicon-base negative material with silane coupling agent and conductive polymer two-layer cladding structure as well as preparation method and application of material
CN103996834A
Preparation method of double-layer composite coated silicon material and lithium ion battery thereof
CN113161528A